The Management Practices and Microbiological Quality of a Dairy Farm with Low Bulk Tank Milk Somatic Cell Count - Risvanli, Ali; Seker, Ibrahim; Saat, Nevzat; Karagulle, Burcu; Koseman, Abdurrahman; Kaygusuzoglu, Erdal (Univ Agriculture, Fac Veterinary Science, 2017)
In this study, we present the management practices and microbiological quality of a dairy farm with low bulk tank milk somatic cell count (BTMSCC). In the mentioned farm, BTMSCC was generally <150,000 cells/mL. BTMSCC per day and bulk tank milk (BTM) microbiological analysis per week were carried out during one year. Weekly animal and udder health controls and management evaluations were performed; the somatic cell counts (SCCs) of the milk samples collected in only 21 weeks of the year were over 150,000 cells/mL but this value was never over 320,000 cells/mL in the herd. When the management practices of the weeks with high BTMSCC were evaluated, negative conditions including changes of paddocks of the animals and estrus synchronization were detected. In the samples taken from the milk collection tank for a total of 22 weeks, microbiological isolation occurred; the most common bacterium was Escherichia coli. Udder hygiene, barn hygiene, the cleanliness of the beddings, the care of the employees toward their work and personal hygiene, and disinfection of the milking machines and their maintenance were all very good for the whole year. During the weekly routine controls, clinical mastitis and teat stenosis were detected twice and once, respectively; however, in those 3 weeks, BTMSCC increased in only the week that the teat stenosis was observed. We observed that, even in farms with intense precautions, BTMSCC may increase and microbiological growth may occur in BTM. To ensure that these situations do not become permanent, these precautions should be applied continuously. (C) 2017 PVJ. All rights reserved
Keywords: Bacteria; Bulk tank milk somatic cell; count; Cow; Management